A CRETAN WOMAN BEKTASHI: “THE CROWNED DERVISH” THE EXAMPLE OF MÜYESSER BACI - ABAYLI, Özcan (SSD Journal, 2022)
Cultural identity and beliefs are one of the most important factors that determine the position of women in socio-cultural life, and therefore, the perspective of today’s societies towards women is shaped within the framework of these historical arguments. As in the family, the use of social rights and freedoms of women, which is the most basic element of society, is increased in proportion to the level of development of societies or is exposed to extreme restrictions, as in the case of the Taliban. In the history of the Turks, the perception of women originating from Central Asia has preserved its dignity by being glorified both before Islam and in the period from the acceptance of Islam through the present. This article discusses the women dervishes in Bektashism, which is one of the Muslim Turkish communities.